2022
DOI: 10.1080/20008198.2022.2057166
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and views of frontline healthcare workers’ family members in the UK during the COVID-19 pandemic: a qualitative study

Abstract: Background The COVID-19 pandemic has had a well-documented negative impact on the mental health and wellbeing of frontline healthcare workers (HCWs). Whilst no research has to date been carried out to explore the challenges experienced by the families of HCWs, some previous research has been conducted with military families, demonstrating that family members of deployed military personnel may also be affected seriously and negatively. Objectives This study aimed to expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Emotional support was the main pillar of support trusted others provided to their first responders (19/24 studies). These studies suggested that fostering a psychologically ‘safe space’ was central to providing emotional support for first responders [ 12 , 38 , 39 , 40 , 41 , 42 , 52 , 53 , 56 ]. This included being present by providing time and emotional capacity [ 37 ], being a ‘sounding board’ [ 40 , 52 ], listening actively [ 42 , 53 , 56 ], expressing acceptance and open-mindedness [ 39 ], observing and recognizing first responders’ emotional condition [ 41 ], and giving first responders space and time to decompress before trusted others’ support provision [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional support was the main pillar of support trusted others provided to their first responders (19/24 studies). These studies suggested that fostering a psychologically ‘safe space’ was central to providing emotional support for first responders [ 12 , 38 , 39 , 40 , 41 , 42 , 52 , 53 , 56 ]. This included being present by providing time and emotional capacity [ 37 ], being a ‘sounding board’ [ 40 , 52 ], listening actively [ 42 , 53 , 56 ], expressing acceptance and open-mindedness [ 39 ], observing and recognizing first responders’ emotional condition [ 41 ], and giving first responders space and time to decompress before trusted others’ support provision [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies suggested that fostering a psychologically ‘safe space’ was central to providing emotional support for first responders [ 12 , 38 , 39 , 40 , 41 , 42 , 52 , 53 , 56 ]. This included being present by providing time and emotional capacity [ 37 ], being a ‘sounding board’ [ 40 , 52 ], listening actively [ 42 , 53 , 56 ], expressing acceptance and open-mindedness [ 39 ], observing and recognizing first responders’ emotional condition [ 41 ], and giving first responders space and time to decompress before trusted others’ support provision [ 42 ]. Some trusted others responded to their first responders’ distress by allowing first responders to dictate the timing and amount of support they were willing to receive [ 42 , 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…With schools and daycare centers closed and one parent in healthcare spending most time away from the home, many children were being raised by a single parent, and because 40% of healthcare workers are married to another healthcare worker, this exacerbated the issue[ 6 ]. Interviews conducted with the family members of healthcare workers revealed that family members had to do more domestic work during the COVID-19 pandemic lockdowns and had extra family responsibilities, such as preparing food and looking after and organizing activities for their children[ 7 ].…”
Section: To the Editormentioning
confidence: 99%
“…The nurses’ families are also suffering from stress, a fear of becoming infected, and psychiatric complaints, especially depression. A study on 208 family members of Hajar hospital employees in Iran found that 71% of participants had moderate depression[ 8 ], and another study reported family members feeling fear and anxiety[ 7 ] because they were constantly worried about the family’s health and were afraid that the healthcare worker would catch COVID-19[ 7 ]. Studies have found that healthcare workers in regular direct contact with patients and their families have an increased risk of contracting COVID-19[ 9 , 10 ].…”
Section: To the Editormentioning
confidence: 99%
“…The current study is commendable for including clinical and non-clinical staff from both acute hospital and mental health Trusts, but other groups were particularly affected by the pandemic. Family members of health-care workers also report a considerable detriment to their own wellbeing due to their loved ones working on the frontline during the pandemic 9 and mental health professionals who were specifically mobilised to support health-care workers have described feeling ill prepared for this work, overwhelmed, and vicariously traumatised. 10 …”
mentioning
confidence: 99%